Selected cardiovascular and psychological changes throughout a competitive season in collegiate female swimmers - Dobson, J.; Harris, B.; Claytor, A.; Stroud, L.; Berg, L.; Chrysosferidis, P. (The Journal of Strength and Conditioning Research, 2020)
Measures that reflect the balance between training-induced fatigue and recovery can provide valuable feedback to help revise training plans. The aim of this study was to use multidimensional measures of the vagal control of the heart rate (HR), psychological stress, and burnout to investigate the impact of overload training and tapering in female swimmers. Thirteen female Division-1 swimmers completed the HR and psychological measures 3 times during a competitive season: (a) at the beginning of the season (BL), (b) eleven weeks later during a period of overload training (OL), and (c) eleven more weeks later and after a taper (TP). Cardiovascular measures included the resting logarithm of the root mean square of successive R-R intervals (lnRMSSD), HR responses to forced breathing (HRdiff), and HR responses to sustained handgrip exercise (HRhg). Psychological measures consisted of the Athlete Burnout Questionnaire and the Recovery-Stress Questionnaire. Repeated measures analyses of variance revealed that sport devaluation, reduced accomplishment, general stress, and emotional exhaustion all increased throughout the season (all were p < 0.05). Also, lnRMSSDrest decreased (p < 0.01) and HRhg increased (p < 0.05) during OL, both of which then returned to BL levels during TP (p < 0.05 and p < 0.01, respectively); whereas HRdiff values fell progressively during the season (p < 0.05). The results indicate that OL impaired cardiac vagal stimulation, and the bulk of evidence indicated that it was fully restored during a TP. In conclusion, lnRMSSD and HRhg were particularly sensitive to changes in workload throughout the season, and so those measures may be especially useful for preventing an excessive accumulation of training-induced fatigue.